Effectiveness of the SMART training intervention on ankle joint function in patients with first-time acute lateral ankle sprain: study protocol for a randomized controlled trial - Janina Tennler; Christian Raeder; Arthur Praetorius; Tobias Ohmann; Christian Schoepp (Trials, 2023)
Abstract Background The lateral ankle sprain (LAS) is the most common injury in the field of everyday and sports-related activities. There is a high rate of patients with LAS who will develop chronic ankle instability (CAI). A possible explanation for this high rate is an insufficient rehabilitation and/or a premature return to intense exercise and workloads. Currently, there are general rehabilitation guidelines for LAS but there is a lack of standardized evidenced-based rehabilitation concepts for LAS, which effectively reduce the high CAI rate. The primary aim of the study is to investigate the effectiveness of a 6-week sensorimotor training intervention (SMART-Treatment, SMART) in contrast to standard therapy (Normal Treatment, NORMT) after an acute LAS on perceived ankle joint function. Methods This study will be a prospective, single-center, interventional randomized controlled trial with an active control group. Patients (14–41 years) with an acute LAS and a MRI confirmed lesion or rupture of at least one ankle ligament will be included. Exclusion criteria are acute concomitant injuries of the ankle, pre-injuries of the ankle, serious lower-extremity injuries of the last 6 months, lower-extremity surgery, and neurological diseases. The primary outcome measure will be the Cumberland Ankle Instability Tool (CAIT). Secondary outcomes include the Foot and Ankle Ability Measurement (FAAM), isokinetic and isometric strength diagnostics, joint repositioning sense, range of motion, measurements of postural control, gait and run analysis, and jump analysis. This protocol will follow the SPIRIT guidance. Discussion Current management of LAS rehabilitation lacks since there is a high rate of patients developing a CAI. It has been shown that exercise therapy improves ankle function in acute LAS as well as in patients with CAI. It is further recommended to address specific impairment domains in ankle rehabilitation. However, empirical data for such a holistic treatment algorithm is missing. Therefore, this study has the potential to improve the healthcare for LAS patients and might be used for a future standardized evidence-based rehabilitation concept. Trial registration “Prospectively registered” ISRCTN – ISRCTN13640422 17/11/2021; DRKS (German Clinical Trials Register) – DRKS00026049.